Peran Gawai Dalam Perkembangan Kognitif Pada Pembelajaran TIK Peserta Didik di SD Al-Irsyad 01 Cilacap - Sarah Yuniantika; Agung Nugroho (Journal on Education, 2024)
In the contemporary human experience, the utilization of mobile devices has become paramount across various domains, particularly in the realm of education. The integration of mobile devices into the educational landscape has permeated schools at all levels, with primary schools demonstrating unique applications and functionalities tailored to their specific grade structures. Moreover, the employment of mobile devices by students undoubtedly exerts an influence on their cognitive development. This research endeavors to investigate the implementation of mobile devices in ICT instruction for students at SD Al-Irsyad 01 Cilacap and to elucidate the role of mobile devices in ICT pedagogy that can potentially impact student achievement at SD Al-Irsyad 01 Cilacap. Employing a qualitative descriptive methodology, this study will engage in the analysis and description of the core research problem, encompassing a diverse range of data and information gathered. The research subjects comprise students from class VC at SD Al-Irsyad 01 Cilacap. Interviews, observations, and documentation serve as the data collection techniques for this study. The findings of this research reveal that the utilization of mobile devices in ICT instruction plays a pivotal role in students' cognitive development, as evidenced by the academic achievements of several students in class VC at SD Al-Irsyad 01 Cilacap. The integration of mobile devices into ICT pedagogy fosters an optimal and interactive learning environment, thereby nurturing students' learning interest.